Costs and benefits of a formal quality framework for colonoscopy: Economic evaluation - Pakneshan, Sahar; Moy, Naomi; O'Connor, Sam; Hourigan, Luke; Messmann, Helmut; Shah, Ayesha; Dulleck, Uwe; Holtmann, G.J. (Endoscopy International Open, 2024)
Background and study aims Reduction of colorectal cancer morbidity and mortality is one of the primary objectives of colonoscopy. Post-colonoscopy colorectal cancers (PCCRCs) are critical outcome parameters. Analysis of PCCRC rates can validate quality assurance measures in colonoscopy. We assessed the effectiveness of implementing a gastroenterologist-led quality framework that monitors key procedure quality indicators (i.e., bowel preparation quality, adenoma detection rates, or patient satisfaction) by comparing the PCCRC rate before and after implementation.Patients and methods Individuals who had a colonoscopy between 2010 and 2017 at a single tertiary center in Queensland, Australia, were included and divided into two groups: baseline (2010–2014) and redesign phase (2015–2017). Data linkage of the state-wide cancer registry and hospital records enabled identification of subjects who developed colorectal cancers within 5 years of a negative colonoscopy. Costs associated with quality improvement were assessed for effectiveness.Results A total of 19,383 individuals had a colonoscopy during the study period. Seventeen PCCRCs were detected. The PCCRC rate was 0.376 per 1,000 person-years and the average 5-year PCCRC risk ranged from 0.165% to 0.051%. The rate of PCCRCs was higher at the beginning (0.166%; 95% confidence interval [CI] 0.15%-0.17%) compared with the later period with full implementation of quality control measures (0.027%; 95% CI 0.023%-0.03%). The quality process determined an incremental cost-effectiveness ratio of -$5,670.53 per PCCRC avoided.Conclusions This large cohort study demonstrated that a formal gastroenterologist-led quality assurance framework embedded into the routine operations of a clinical department not only reduces interval cancers but is also cost-effective regarding life years gained and quality-adjusted life years.
Keywords: Endoscopy Lower GI Tract; Colorectal cancer; CRC screening; Quality and logistical aspects; Performance and complications